ANALISIS KEPEMIMPINAN NON MUSLIM MENURUT FIQIH DAN HUKUM TATA NEGARA DI INDONESIA - Siti Qoniah; Ashif Az Zafi (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The leader is the most important figure in a sphere of community life, both small and broad, the progress of a sphere of society depends on how the leader in bringing the country, whether it is more advanced, prosperous or vice versa. Therefore, it is the responsibility of all of us as a citizen to be selective in choosing a leader. Islam as a religion of revelation for Muslims and make it as a guide in carrying out their lives, including in political matters, namely becoming a leader. The leader has an important position in Islam. In the Islamic view of non-Muslim leaders, there are differences of opinion of the scholars about the legitimate or non-Islamic leaders in the Islamic perspective. The difference in opinion is due to the perception in understanding the verses about saints or awliya 'mentioned in the Qur'an Moreover, the current reality of the state of Indonesia is not an Islamic state, but a democratic state, which has a majority of its citizens, who are Muslim. In Indonesia, to become a leader in positive law and in the Constitution, there is no explanation which explains that the requirements to be a leader in Indonesia must be religious and prohibit non-Muslim religion. the opening of the 1945 Constitution only explained that in Indonesia there was no difference between ethnicity, religion, language, culture, etc. Therefore, it is necessary to conduct a deeper study in understanding it so that there is no misunderstanding among the people.Keywords: Leaders; Indonesia; Islam; Non-Muslims; Constitution